The relationship between cumulative grade point average achievement and time management skills among students at higher learning institution / Normala Ismail and Mohamad Kamil Ariff Khalid - Ismail, Normala; Ariff Khalid, Mohamad Kamil (Universiti Teknologi MARA, Kedah, 2020)
Time management skills are one of the key learning skills that students can master in order to help them achieve excellence while studying at universities. However, a thorough study of the extent to which this skill is owned by students and the impact on their academic performance is rarely focused especially among Universiti Teknologi MARA students. Hence, this paper examines the issue based on a study of 200 diploma level students from three faculties in various programs studying at Universiti Teknologi MARA Pahang Branch Raub Campus. Data were collected using a set of questionnaires and analyzed descriptively using t-test, ANOVA and Pearson’s Correlation. The findings show that in general, time management skills among students are moderate and these skills differ significantly between gender and program of study. This study also found a significant relationship between time management skills and the students Cumulative Grade Point Average.